TdT Expression Is a Marker of Better Survival in Merkel Cell Carcinoma, and Expression of B-Cell Markers Is Associated With Merkel Cell Polyomavirus. Issue 1 (5th March 2020) - Hoang, Mai P; Donizy, Piotr; Wu, Cheng-Lin; Kopczynski, Janusz; Pieniazek, Malgorzata; Miller, David M; Ryś, Janusz
Abstract: Objectives: Merkel cell carcinoma is a rare but very aggressive cutaneous tumor. We evaluated the prognostic potential of B-cell markers (terminal deoxynucleotidyl transferase [TdT], PAX5, CD117), follicular stem cell markers (CK15, CK19), p63, p53, RB, and Merkel cell polyomavirus (MCPyV; CM2B4) in 136 primary cutaneous Merkel cell carcinomas. Methods: Clinical, histopathologic, and immunohistochemical analyses were performed. The results were correlated with patient outcomes by Fisher exact test, log-rank tests, and Cox multivariate models. Results: By Fisher exact test, although TdT significantly correlated with both lack of progression ( P = .0087) and alive status ( P = .0056), MCPyV status correlated only with alive status ( P = .031). In univariate analyses, TdT, MCPyV, and RB significantly correlated with improved overall survival, whereas p63 and CK15 correlated with worse overall survival. However, in multivariate analyses, only TdT expression remained as an independent predictor of improved overall survival, Merkel cell carcinoma-specific survival, and progression-free survival. By linear regression analyses, significant correlations between MCPyV vs TdT, PAX5, and CD117 were observed. Conclusions: TdT expression is a potential marker of better survival in Merkel cell carcinoma. Expression of B-cell markers is associated with MCPyV, suggesting that clonal viral integration might play a role in the expression of these markers.